Endless Quilt, object range - Forlano, Penelope (FORM, 2012)
This project contributes to the discourse on consumer behaviour by exploring person-object relationships through co-creation, and an object 'becoming' as a construct. Made of reclaimed and new materials, and constructed in a modular, potentially endless patchwork, this quilted wall object reflects the idea if the family heirloom, memory and the quilted form.